Ligand-Free Palladium-Catalyzed Hydroxycarbonylation of Aryl Halides under Ambient Conditions: Synthesis of Aromatic Carboxylic Acids and Aromatic Esters - Han, Wei; Jin, Fengli; Zhou, Qing (Synthesis, 2015)
Aryl halides were readily converted into their corresponding aromatic carboxylic acids in high yields with high selectivity by ligand-free palladium-catalyzed hydroxycarbonylation at room temperature and atmospheric pressure. The new method is operationally simple and scalable. In addition, aromatic esters were easily synthesized through one-pot hydroxycarbonylation/alkylation with alkyl halides.
Keywords: aryl halides; carbonylation; carboxylic acids; hydroxycarbonylation; palladium